Epithelial cell polarity affects susceptibility to Pseudomonas aeruginosa invasion and cytotoxicity. - Fleiszig, S M (1997)
Intact tissues are relatively resistant to Pseudomonas aeruginosa-induced disease, and injury predisposes tissue to infection. Intact epithelia contain polarized cells that have distinct apical and basolateral membranes with unique lipids and proteins. In this study, the role of cell polarity in epithelial cell susceptibility to P. aeruginosa virulence mechanisms was tested. Madin-Darby canine kidney (MDCK) cells, human corneal epithelial cells, and primary cultures of two different types of airway epithelial cells were grown on Transwell filters or in plastic tissue culture wells. P. aeruginosa invasion of cells was quantified by gentamicin survival assays with two isolates that invade epithelial cells (6294 and PAO1). Cytotoxic activity was assessed by trypan blue exclusion assays with two cytotoxic strains (6206 and PA103). Basolateral surfaces of cells were exposed by one of two methods: EGTA pretreatment of epithelial cells or growth of cells in low-calcium medium. Both methods of exposing basolateral membranes increased epithelial cell susceptibility to P. aeruginosa invasion and cytotoxicity. Migrating cells were also found to be more susceptible to P. aeruginosa invasion than confluent monolayers that had established membrane polarity. Monolayers of MDCK cells that had been selected for resistance to killing by concanavalin A were resistant to both cytotoxicity and invasion by P. aeruginosa because they were more efficiently polarized for their susceptibility to P. aeruginosa virulence factors than regular MDCK cells and not because they were defective in glycosylation. These results suggest that there are factors on the basolateral surfaces of epithelial cells that promote interaction with P. aeruginosa or that there are inhibitory factors on the apical cell surface. Thus, cell polarity of intact epithelia is likely to contribute to defense against P. aeruginosa infection.